ANALISIS USAHA KERUPUK SAGU DI TIMBALUN KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG STUDI KASUS: USAHA KERUPUK SAGU JASO MANDIRI (Analysis Of The Sago Cracker Business In Timbalun Bungus District, Teluk Kabung District, Padang City Case Study: Jaso Mandiri Sago Cracker Business) - LEOVITA, ANGELIA; DEPERIKY, DEDED; AULIA, RIZKA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2025)
This study aims to 1) describe the profile of Jaso Mandiri Sago Cracker Business 2) analyze Cost of Goods Sold 3) Analyze Revenue and Profit 4) Analyze Business Feasibility. This study uses a case study method with a purposive sampling technique in Jaso Mandiri Sago Cracker Business. The data used consists of primary and secondary data. Data analysis was carried out descriptively-qualitatively and quantitatively, with a qualitative descriptive analysis approach, Cost of Goods Sold Analysis, revenue and profit analysis, business feasibility analysis using R/C B/C BEP Unit, BEP Price, BEP Revenue. The results of the study indicate that the profile of the Jaso Mandiri Sago Crackers Business is a family business that has been operating for 10 years with a traditional production system. The Cost of Goods Sold of Rp 588.66 per unit indicates a fairly good production cost efficiency. Income analysis shows a total Income of Rp 1.868.852,15 with a net profit of Rp 1.364.853,26 per production period. The R/C ratio of 1.45 indicates that every rupiah invested generates a revenue of Rp 1.45, indicating the business is financially feasible. The B/C ratio of 0.45 indicates a positive net profit. The Break Even Point analysis shows a BEP Unit of 1,186.61 units, a BEP Price of Rp 689.81, and a BEP Revenue of Rp 1,186,608.11. Based on all feasibility indicators, this business is feasible to run.